Dopaminergic System: Selected Advances and Emerging Potential Therapeutic Targets - Abdelaziz Ghanemi (International Journal of Public Health Science (IJPHS), 2013)
Studies on different physiological and pathophysiological properties of the dopaminergic system have led to novel evidences and theories that suggest the possible targeting of such system in a variety of pathologies and disorders. Herein, we illustrate the applications and the therapeutic importance that such findings and advances might have. We hope that the content of this work will guide researches devoted to dopaminergic aspects that combine neurosciences with pharmacology.DOI: http://dx.doi.org/10.11591/ijphs.v2i2.3070